The impact of the planter box construction to the building / Aidatol Norshila Abdul Aziz - Abdul Aziz, Aidatol Norshila (Faculty of Architecture, Planning and Surveying, 2008)
Planter boxes reduce impervious cover by retaining stormwater runoff rather than allowing it to directly drain into nearby sewers. There are three main types of planter boxes: Flow through, Contained and infiltration. Planter boxes can play an important role in the city by minimizing stormwater runoff, reducing water pollution, and creating a greener and healthier look. But, the main purposes of planter box built in building are to enhance overall landscape aesthetics and to supply the building with the natural environment. Planter boxes can be used on sidewalks, plazas, rooftops and other otherwise impervious areas. They can also be constructed alongside buildings, provided proper waterproofing measures are used to protected structure of building. The intention of this research is to study the impact of planter boxes construction to the building. It consists of the good or bad impact may occur from the construction at the case study and also to know the suitability of planter boxes built in building. This research involves observation, interview and questionnaire methodology. The observation on the condition of the planter boxes and interview will be carried out to the maintenance management department of each building are done at the Perbadanan Putrajaya, Putrajaya International Convention Center (PICC) and Ministry Energy, Water & Communication (MEWC). The questionnaire will de developed to be completed by architects, engineers, builders and contractors, and developers. Perspectives of professionals involved in various aspects of the building process; business, design, and technical implementation are a must in order to conduct a full spec research for this academic project. It was to examine the perceptions of the professional group about the planter boxes construction. The distribution of questionnaire will be focused on a group of building professionals whom are at least having some involvement in construction industry.